Bioactive Functionalisation of Silicones with Polysaccharides - Bračič, Matej; Strnad, Simona; Fras Zemljič, Lidija; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book covers the functionalisation of silicone surfaces with polysaccharides to improve their antimicrobial and antifouling properties, thus reducing the implant-related infections. The authors describe how silicone surfaces were chosen because silicone exhibits excellent biocompatible properties and is already being used for medical implants such as catheters, breast implants, prosthetics etc. The potential of polysaccharides such as cellulose, chitosan, hyaluronic acid, and other natural substances such as natural surfactants as coatings for silicones are also discussed, their effects are evaluated. With the aging of the population, the number of medical implants is growing and with it the number of infections associated with the use of implants.
Introduction -- Silicone in medical applications -- Catheter associated urethral tract infections -- Polysaccharides in medical applications -- Functionalisation of silicones with polysaccharides -- Conclusions.
Keywords: Surfaces (Technology).; Thin films; Polymers; Biomedical engineering; Surfaces, Interfaces and Thin Film; Polymers; Biomedical Engineering and Bioengineering